Neoconstitucionalismo, nuevo constitucionalismo latinoamericano y procesos constituyentes en la región andina - Jorge Benavides Ordóñez (Ius Humani. Jornal do direito, 2016)
The purpose of the paper is to account for the importance attributed by the constitutions inspired by the so-called new Latin American constitutionalism to popular participation in matters of constitutional changes. To that extent, the analysis will be carried out in a comparative manner. To this end, in the first place, we differentiate between neoconstitutionalism and new Latin American constitutionalism. Later, we describe the influence of the new Latin American constitutionalism in the processes of creation and reform of the Constitutions of Colombia, Venezuela, Ecuador and Bolivia. Next Chapter is dedicated to Ecuador, one realizes the present inconsistency in terms of participation that exists between the model contemplated in the constitutional text and political and legal practice. Finally, there are five conclusions that shows the future way for a true participation in regional neoconstituionalism and some contradictions between dogmatic and organic part of Ecuadorian Constitution.